Inequities in visual health and health services use in a rural region in Spain - Sergio Latorre-Arteaga; José Fernández-Sáez; Diana Gil-González (Elsevier, 2018)
Objective: To analyse perceived visual health and health services use in a rural population in relation to socioeconomic characteristics and compared with the general population in Spain. Method: Cross-sectional study in a rural population using a structured questionnaire including questions comparable to the Spanish National Health Survey (2012). A descriptive analysis was carried out through the calculation of frequencies and prevalence, the χ2 test for independent variables, contrasts of proportions and logistic regression to obtain associations between the rural and general populations and socioeconomic variables. Results: For the rural population studied, the prevalence of poor perceptions of visual health is 40.8% in men and 39.4% in women, and is strongly associated with age, employment situation, income and presence of chronic diseases (p ˂0.001). Compared with the general population, the rural population has a higher risk of presenting with serious difficulties related to farsightedness (OR: 2.56; 95% CI: 1.32-4.95) and make less use of optical correction (OR: 0.57; 95%CI: 0.44-0.74). The use of health services is not sufficient for adequate prevention, particularly in diabetics. For those affected by poor vision, the distance to travel to receive an eye exam, the belief that eyesight problems come with age and the cost of glasses are the principal reasons used to explain why eyesight problems are not resolved. Conclusions: The rural population presents worse visual health that is influenced by social and economic factors. Improving accessibility and reducing barriers is essential to tackle avoidable visual disability and reduce health inequities. Resumen: Objetivo: Analizar la salud visual y el uso de servicios de salud en una población rural periférica en relación a variables socioeconómicas y a la población general española. Métodos: Estudio transversal en población rural con administración de cuestionario estructurado incluyendo preguntas comparables a la Encuesta Nacional de Salud en España (2012). Se realizó un análisis descriptivo a través del cálculo de frecuencias y prevalencias, el uso de la prueba χ2 para la independencia de variables y el contraste de proporciones y regresión logística para obtener asociaciones entre variables en población rural y general. Resultados: En la población rural estudiada, la prevalencia de mala salud visual percibida es del 40,8% en los hombres y del 39,4% en las mujeres, y está fuertemente asociada a la edad, la situación laboral, el nivel de ingresos y la presencia de enfermedades crónicas (p ˂0,001). Presentan mayor riesgo de afrontar importantes dificultades en visión lejana (odds ratio [OR]: 2,56; intervalo de confianza del 95% [IC95%]: 1,32-4,95) y hacen un menor uso de corrección óptica (OR: 0,57; IC95%: 0.44-0.74) en comparación con la población general. El uso de los servicios de salud es insuficiente para una adecuada prevención, particularmente en las personas diabéticas. Aquellos/as con dificultades visuales señalaron la distancia al centro de salud, asociarlo a la edad y el precio de las gafas como principales barreras en el acceso a una solución. Conclusiones: La población rural presenta peores indicadores de salud visual, influenciados por factores socioeconómicos. Se requieren acciones que aborden la discapacidad visual por causas evitables y reducir las inequidades en salud. Keywords: Rural population, Vision disorders, Health services, Social determinants, Palabras clave: Población rural, Salud visual, Servicios de salud, Determinantes sociales